Elucidating the microbial community associated with the protein preference of sludge-degrading worms. Issue 2 (15th January 2019) - de Valk, Steef; Feng, Cuijie; Khadem, Ahmad F.; van Lier, Jules B.; de Kreuk, Merle K.
ABSTRACT: Sludge predation by aquatic worms results in an increased sludge reduction rate, which is mainly due to the specific removal of a protein fraction from the sludge. As microorganisms play an essential role in sludge hydrolysis a better understanding of the microbial community involved in the worm predation process will provide more insight into the relations between the aquatic worms, their associated microbiome and the efficient sludge reduction. In this study, the microbial community associated with predation by the Tubifex tubifex was investigated. The microbial diversity in the samples of the worm faeces (WF), predated activated sludge and protein-rich substrates were compared. The results indicated that predation on sludge resulted in a microbial change from Actinobacteria (44%) in the sludge, to Proteobacteria (64%) and Bacteriodites (36%) in the WF. Interestingly, the faecal microbial community was more related to the community in (predated) protein-rich substrates than to the community in predated or endogenously respirated activated sludge samples. This similar microbial community could be due to microbial utilisation of protein hydrolysis products. Alternatively, conditions in the worm gut could facilitate a protein hydrolysing community which assists in protein hydrolysis. The genera Burkholderiales, Chryseobacterium and Flavobacterium were found to be associated with predation by T. tubifex .